Ultimate strength of glued-laminated timber beam - Baharudin, Khairul Salleh (1996)
Bending strength of timber beam has been the subject of interest ever since timber was used for structural purpose. Many studies have dealt with the strength prediction of timber beams in which compression and tension properties of timber were being correlated to their behaviour in bending. Issues relating to the bending strength models, stress-strain distribution, movement of neutral axis, modulus o f elasticity, the proportional limit stress, the extreme fibre-tension stress, and the size effects of timber beams, put forw ard by many researchers, were focused on softwood timber of western countries None thus far, has been verified for the hardwood species of local origin This study present the verification of the ultimate bending strength models on local Dark Red Meranti (DRM) timber The applicability of strength models proposed by Zakic, Bazan. and E3uchanan on solid and gluedlaminated (glulam) DRM beams are examined. Some of the findings prompted by previous researchers are observed in this study. The proposed modifications to the Bazan's and Buchanan's model have significantly improved the strength prediction of DRM beams.